2018
DOI: 10.4236/oalib.1104876
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Factors Associated with the Use of Aphrodisiacs among Adult Male Residents in Ashaiman Municipality, Ghana

Abstract: Background: There is limited scientific evidence supporting the efficacy of aphrodisiacs and more worrying is the fact that potential adverse health effects could result from the abuse of aphrodisiacs. Despite the safety concerns raised by the FDA on the abuse of unregistered sex enhancing products, the patronage remains high amidst debilitating side effects. We explore the factors influencing the use of aphrodisiacs while assessing the prevalence of aphrodisiac usage among men in the Ashaiman Municipality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 11 publications
4
14
0
4
Order By: Relevance
“…The results indicated that among all studied sample who had participated in the current study, 38.2% of participants had used the aphrodisiacs. The results of the current study were supported by the study ofManortey, (2018) who reported that about half of the participants (53%) ever using Aphrodisiacs, also a study investigated the indiscriminate use of sex enhancing products among Ghanaians, showed 61% of males were using Aphrodisiacs(Danquah, 2011), Moreover, high usage has been reported by Ahmed et al , (2017). A study by Makwana et al, (2013) showed a lower prevalence (26%) in an online based survey.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The results indicated that among all studied sample who had participated in the current study, 38.2% of participants had used the aphrodisiacs. The results of the current study were supported by the study ofManortey, (2018) who reported that about half of the participants (53%) ever using Aphrodisiacs, also a study investigated the indiscriminate use of sex enhancing products among Ghanaians, showed 61% of males were using Aphrodisiacs(Danquah, 2011), Moreover, high usage has been reported by Ahmed et al , (2017). A study by Makwana et al, (2013) showed a lower prevalence (26%) in an online based survey.…”
supporting
confidence: 83%
“…The results of the current study were supported by Mensah, (2018) who reported that the high level of knowledge and the healthy life style are protective factors from using the aphrodisiacs. Similar results have also reported that respondents who have level of knowledge on the associated side effects of usage the aphrodisiac drugs were 0.8 times less likely to use the drug compared to their counterparts who admitted having no knowledge (Manortey, et al, 2018). This might be so because participants who have satisfactory level of knowledge regarding aphrodisiacs and healthy life style might enhance their awareness and attitudes and understand the risks, side effects and complications of these medications.…”
Section: Discussionsupporting
confidence: 62%
“…Many developing countries in the last decade have witnessed increasing trends in the misuse of psychoactive substances with tramadol becoming the major drug in these countries including Ghana [ 6 , 16 ]. Tramadol manifests some effect characteristic close to that of opioid agonists, and its misuse seems to be a problem for Ghana as several reports on the side effects of the drug, especially when taken in higher doses including nausea and vomiting, constipation, sweating, dizziness, seizures and postural hypotension, among others continue to build-up [ 5 , 6 , 16 , 38 – 40 ] . Our study contributes to the existing literature in various ways.…”
Section: Discussionmentioning
confidence: 99%
“…As in many other sub-Saharan African countries, the commonly used sexual enhancement drugs that are approved by the national regulatory body in Ghana (i.e., Food and Drug Authority, FDA) often take the form of alcoholic/non-alcoholic drinks (e.g., Adonko bitters and Alomo bitters) and pills/capsules (e.g., Angel Natural Capsule, Kingdom Ginseng Power Capsule) usually made from herbal ingredients. Unapproved substances include alcoholic and non-alcoholic mixtures, with the main ingredients being herbs such as mahogany, ginger, aidan fruit, and West African black pepper [ 2 , 7 , 8 ]. Other users mix acholic substances with drugs such as paracetamol and tramadol.…”
Section: Introductionmentioning
confidence: 99%